Climate factors determine the utilization strategy of forest plant resources at large scales - Wang, Jiangfeng; Wang, Xianxian; Ji, Yuhui; Gao, Jie (Frontiers in Plant Science, 2022)
The functional traits of plants are a visual representation of plant resource utilization strategies. Plants with higher specific leaf area (SLA) and lower leaf dry matter content (LDMC) exhibit "faster investment-return" resource utilization strategies. However, the distribution patterns and driving factors of plant resource utilization strategies at the macro-scales are rarely studied. We explored the relative roles of climatic and soil factors in shaping plant resource utilization strategies at different vertical levels of the forest using data at 163 sites from 926 forests in China. We show that SLA and LDMC of plants at different vertical levels differed significantly (P < 0.05). Resource utilization strategies showed significant geographical differences, with the western arid regions being more conservative in their use of plant resources, adopting a "slower investment-return" survival strategy, while in areas with abundant hydrothermal conditions, plant resource utilization shifted to a "faster investment-return" survival strategy. With the increase in temperature and the decrease in rainfall, SLA decreases significantly (P < 0.05), and the resource utilization mode is gradually conservative. The MAP is a key climatic factor that dominates the resource utilization strategies of plants at the macro-scales. Plants use resources more conservatively as soil pH increases. Climate and soil factors together determine the resource utilization strategies of plants at different vertical levels at the macro-scales, but the relative contributions of both depend on the type of life form. Our findings provide some theoretical support for understanding the impact of global warming on plant resource utilization.